(untitled) (Jurnal Ekonomi dan Kebijakan Pembangunan, 2021)
ASEAN-China Free Trade Area (ACFTA) is an agreement with ASEAN countries with China to establish a free trade area. Telephones are the main commodity in China which is included in the largest import category in ASEAN, where the value of imports of cellphones from China is higher than other countries, China dominates the import of cellphones in ASEAN with 55% o ea (ACFTA) on telephone imports from ASEAN countries in China. This study uses annual data from 2006 to 2020f total imports from other countries. This study aims to analyze the influence of the ASEAN-China Free Trade Ar. The methods used in this research are descriptive analysis and gravity model. Quantitatively, it shows that the production of telephones in each ASEAN country has not met the demand for telephones, so imports are carried out. The estimation results of the gravity model show that the ACFTA variable has no significant effect on China’s telephone imports to ASEAN. Other factors that affect China’s telephone imports to ASEAN are ASEAN’s real GDP, China’s real GDP, real exchange rate, distance and inflation affect China’s telephone imports to ASEAN.